2020
DOI: 10.1002/alz.046618
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion of dementia risk education

Abstract: Background The Preventing Dementia Massive Open Online Course (PD‐MOOC) is one of several initiatives aiming to increase dementia risk knowledge and promote risk‐reducing behaviour. These initiatives primarily reach advantaged individuals, increasing health inequities. Previously, thematic analysis of PD‐MOOC participant feedback identified frequent reports of sharing dementia risk information with others. Interpersonal communication often introduces information to people from a broader demographic and may inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We anticipate that this targeted and supported recruitment strategy will increase the representation of people who may not otherwise join a web-based research program and whose data will contribute to more population-equivalent distributions across the risk domains (eg, smoking, BMI, diet). A related study [ 67 ] is examining the drivers of reach and resonance of risk reduction messages at community and population level and will inform the ongoing development and dissemination of actionable information about dementia risk reduction. Cultural and linguistic diversity was not included in the initial baseline data but is increasingly recognized as an important determinant of health and health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that this targeted and supported recruitment strategy will increase the representation of people who may not otherwise join a web-based research program and whose data will contribute to more population-equivalent distributions across the risk domains (eg, smoking, BMI, diet). A related study [ 67 ] is examining the drivers of reach and resonance of risk reduction messages at community and population level and will inform the ongoing development and dissemination of actionable information about dementia risk reduction. Cultural and linguistic diversity was not included in the initial baseline data but is increasingly recognized as an important determinant of health and health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Some participants in dementia risk-reduction initiatives report discussing these initiatives in personal conversations. In the preventing dementia MOOC, 70% of participants reported hearing about the programme through interpersonal communication, which is unsurprising given that 99% of participants stated that they would recommend the MOOC to others [34]. According to the predictions of the reviewed models, these personal conversations may already be broadening the reach of this initiative.…”
Section: Focusing On Interpersonal Communicationmentioning
confidence: 99%
“…While empirical data have shown that two of the identified strategies are able to broaden the reach of dementia risk-reduction initiatives, there is no data to suggest that these strategies will promote initiative participation among all members of a global target audience. Interpersonal conversations may transmit information about dementia risk reduction alongside information about risk-reduction initiatives, which may independently increase dementia risk-reduction knowledge and promote risk-reducing behaviour, thereby reducing the importance of direct initiative participation [34]. Interpersonal communication may therefore have the added benefit of enabling people who may never participate in dementia risk-reduction initiatives to access and act on information about dementia risk reduction.…”
Section: Utilising Dissemination Agentsmentioning
confidence: 99%
“…19,20 Similar to other dementia risk reduction initiatives, the Wicking Dementia Centre's globally available Preventing Dementia Massive Open Online Course (MOOC) primarily attracts people aged 50-70, women, health care workers, highly educated people, and people from high-income countries. 19,21 Preventing Dementia MOOC participants frequently report sharing information with others as an outcome of course participation. After completing the MOOC, 99% of responding participants stated that they would recommend the MOOC to others.…”
Section: Introductionmentioning
confidence: 99%
“…Preventing Dementia MOOC participants frequently report sharing information with others as an outcome of course participation. After completing the MOOC, 99% of responding participants stated that they would recommend the MOOC to others 21 . In MOOC iterations from 2016 to 2018, sharing information from or about the MOOC was one of the most common topics arising in free‐text responses to the broad application question: “if you have already applied your MOOC learning, please tell us how.” 22 This interpersonal communication may be reaching people from a broader range of backgrounds than those directly participating in the course, increasing the population‐wide impact of this initiative.…”
Section: Introductionmentioning
confidence: 99%